Strategi Pengembangan Laboratorium Business Venturing: (Studi Kasus Pada Fakultas Ilmu Administrasi Universitas Brawijaya) - Arik Prasetya; Astri Warih Anjarwi; Kartika Putri Kumalasari; Nabilla Putri Lishandy (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The laboratory plays an important role in the learning process, especially in learning collages. Business Venturing Laboratory at the Faculty of Administration, University of Brawijaya, supports the achievement of learning outcomes in every study program in the business administration department, including: department of business administration, tourism department, and taxation department. Based on the data, the number of students majoring in business administration has increased on average every year, but it has not been accompanied by an increase in laboratory facilities and infrastructure. In addition, the department is not only aimed at deepening student competencies but also aims to achieve the vision and mission of the business administration department, which is to produce graduated students superior and dignified business administration and have intellectual abilities in the field of business administration based on Pancasila values. Therefore, it is necessary to formulate a venture business laboratory development strategy. This study is expected to provide input to FIA UB regarding the formulation of development strategies FIA UB Business Venturing Laboratory.